The impacts of motives, barriers, and behaviour on the travel package attractiveness from Muslim travelers perspectives - Ahmad, A.; Izian Idris, *; Mason, C.; Hasim, M. A.; Sajilan, Sulaiman (Blue Eyes Intelligence Engineering and Sciences Publication, 2020)
Travel agencies have modernized the way they communicate their package tours to travelers through digital technology. It is however imperative to also understand travelers' needs in order to remain competitive in the market. In particular, it is crucial to clearly recognize the diversity in travel needs particularly the travel desires of Muslims travelers since they hold a different set of values and beliefs that guide their travel needs. Hence, this research attempts to understand Islamic travel needs among Muslim travelers and how such needs can impact the attractiveness of package tours in Malaysia. The travel needs of Muslim travelers i.e. travel motives, travel behavior and perceived travel barriers will be determined against the attractiveness of packaged tours. This paper proposes a conceptual model so that further analyses can be conducted and marketing strategies can be recommended to enhance the attractiveness of package tours developed by Travel agencies for Muslim travelers. By gaining a better understanding of Muslim traveler needs, tour operators in Klang Valley, Malaysia will be able to enhance their marketing strategies, increase the attractiveness and demand for their package tours and attract more Muslim travelers to travel with them.